The inhibitory effect of intraspinal microstimulation of the sacral spinal cord on nonlinear bladder reflex dynamics in cats - Qasemi, Amirhossein; Aminian, Alireza; Erfanian, Abbas (Frontiers in Neuroscience, 2025)
ObjectiveElectrical stimulation of the pudendal nerve, pelvic nerve, sacral dorsal root ganglion (DRG), and spinal cord has been explored to treat urinary incontinence and overactive bladder (OAB). This study introduces sacral intraspinal microstimulation (ISMS) as a novel method to inhibit spontaneous bladder reflexes in anesthetized cats. In addition, we investigated the effects of intermittent and switching stimulation patterns on bladder inhibition.MethodsThe electrode was implanted in the dorsal horn of the S2 spinal cord. Bladder pressure was recorded under isovolumetric conditions, and the stimulation parameters were adjusted to inhibit spontaneous bladder contractions. Nonlinear dynamic methods, including chaos theory, were employed to analyze the complexity of bladder reflexes.ResultsResults demonstrated that ISMS targeting the dorsal horn of the S2 spinal segment effectively suppressed high-amplitude spontaneous contractions. Furthermore, bladder reflexes exhibited complex dynamics, ranging from regular to chaotic patterns, with transitions between these states. Importantly, ISMS was able to stabilize these chaotic dynamics, leading to more controlled bladder behavior.ConclusionThese findings suggest that sacral ISMS offers a promising, targeted alternative to traditional stimulation therapies, potentially providing a new therapeutic approach for managing OAB and urinary incontinence by regulating chaotic bladder activity.